Profil Dukungan Sosial Pada Remaja di SMK Negeri X Surakarta - Annisa Siti Solikah Satriadanie; Faqih Purnomosidi; Sri Ernawati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Adolescence is a challenging period, particularly in terms of social adjustment and identity search. A lack of social support from family and friends can lead to emotional distress and poor psychological conditions in adolescents, as observed in the students of SMK Negeri X Surakarta. This study employs a descriptive qualitative approach with purposive sampling, involving seven students and two school counselors as informants. Data were collected through surveys, in-depth interviews, and observations, then analyzed based on five aspects of social support. The findings reveal that emotional support, peer support, and instrumental support related to economic conditions are very limited, which leads to emotional stress and tendencies to withdraw. However, the presence of alternative figures, such as the school counselors and other family members, helps alleviate the psychological burden on adolescents. The study concludes that insufficient social support contributes to emotional stress and a decline in academic performance. Therefore, it is crucial for families, schools, and social environments to play an active role in building a responsive and sustainable support system to address these issues.